The analysis of factors to predict eating behavior among adolescent girls: A community-based study in Indonesia - Dian Isti Angraini; Fitria Saftarina; Sofyan Musyabiq Wijaya (Alma Ata University Press, 2023)
Background: The eating behavior of adolescent girls is often not concerned with the nutritional content of food, consuming more fast food, causing changes in eating behavior leading to unhealthy eating behavior. The impact of unhealthy eating behavior is the emergence of obesity and underweight. Adolescent eating behavior is influenced by predisposing, supporting, and reinforcing factors.Aims: This study aims to analyze the factors to predict the eating behavior of community-based adolescent girls in Indonesia.Method: This study uses a quantitative method with a cross-sectional approach. The sample consisted of 210 adolescent girls aged 15-18 years in the city of Bandar Lampung, Indonesia. Data were taken from July to October 2022. The sample was taken using the multistage random sampling method and analyzed using the chi-square test and logistic regression.Results: As many as 75 adolescent girls (35.7%) have unhealthy eating behavior, 164 people (78.1%) have poor nutritional knowledge, 6 people (2.9%) experience early menarche, 98 people (46.7%) were malnourished, 99 people (47.1%) had an eating disorder, 74 people (35.2%) had a risky personality, 109 people (51.9%) were dissatisfied with their body image, 100 people (47.6%) had a low allowance, 109 people (51.9%) influenced by social media, 98 people (46.7%) influenced by idols, 136 people (64.8%) influenced by family, 111 people (52.9%) influenced by teachers, and 76 people (36.2%) were influenced by their peers. Statistically, the factors related to the eating behavior of adolescent girls were knowledge (p=0.016), nutritional status (p=0.000), eating disorder (p=.0.008), personality (p=0.002), body image (p= 0.006), allowance (p=0.11), social media (p=0.000), idol figures (p=0.03), family (p=0.037), teachers (p=0.048) and peers (p=0.000 ), while menarche was not related (p=0,241). The most associated factors in predicting the eating behavior of adolescent girls are nutritional status, eating disorders, personality, body image, social media, idol figures, teachers, and peers.Conclusion: The prevalence of unhealthy eating behavior in adolescent girls is 35.7% and the most associated factors in predicting the eating behavior of adolescent girls are nutritional status, eating disorders, personality, body image, social media, idol figures, teachers, and peers.